Gabonese French Dictionaries: Survey and Perspectives - Mavoungou, Paul Achille (Lexikos, 2013)
This article is a survey study of lexicographic activities with regards to the French language as it is spoken in Gabon, a French-speaking country in central Africa. The French language as it is spoken in Gabon does not only refer to Gabonisms (mostly items derived from native Gabonese languages), but also to standard French, official French (acrolectal level), common French (mesolectal level) and popular French (basilectal level). All four levels are present in French as it is used in Gabon. In other words, the Gabonese have named the realities of their own environment with lexical items coined on their own soil or borrowed from other languages. This has strengthened and enriched French as it is spoken in Gabon. The modern era of Gabonese lexicography has witnessed the production of various dictionaries focusing on this African variety of French. Before 1999, in Gabon and due to the status of French as the sole official language of the country, French dictionaries used in Gabon were mostly French products. Monolingual French dictionaries produced in Gabon by Gabonese scholars include a very limited number of authors, namely: Dodo Bounguendza (2008), Ditougou (2009) and Moussounda Ibouanga (2011).Despite the fact that these dictionaries were compiled for use by Gabonese, they are differential as they tend to include references of the Parisian standard French. Indeed, a differential dictionary is a dictionary focusing on differences between two language varieties or two similar languages, and current Gabonese French dictionaries are by all means differential. It is this situation, and the ways it can be corrected that this article will focus on. The idea is to produce a complete dictionary of variant B, namely Gabonese French. Such a dictionary will reflect certain emancipation from the French language spoken in France (i.e. Parisian standard French), herein referred to as variant A.